OCEANOGRAPHIC OF THE FISHING GROUND FOR ANOCHVY (Stolephorus spp.) IN THE KOLONO BAY, SOUNTH KONAWE DISTRICT - Resky Dwi Angraeni; Naslina Alimina; Muslim Tadjuddah (Jurusan Perikanan dan Kelautan, 2023)
Kolono Bay is one of the waters in South Konawe Regency which has a large potential for fishery resources with an area of ± 9,400 hectares of water. One of the leading commodities in the waters of Kolono Bay is anchovy (Stolephorus spp). This study aims to determine the characteristics of oceanography, namely the parameters of pH, Salinity, DO (Dissolved Oxygen), current velocity, and depth of anchovy fishing area in the waters of Kolono Bay. This study uses a direct measurement method in the field. Data collection and analysis were carried out from January to March 2019 with ten research stations. The results showed that in January, February, and March in the waters of Kolono Bay, the water temperature ranged from 28.47-31.67°C. The current velocity has a range between 0.092-0.508 m/s. The value of water depth has an average value of 8.0-17 m, the average value of dissolved oxygen ranges from 4.91-7.07 mg/L, salinity with an average value of each station ranging from 32.90-35.63‰ and The degree of acidity of the water (pH) has an average of 8.00. The suggestion from this study is the need for further research on the study of status of anchovy utilization in Kolono Bay so that sustainable and sustainable management can be carried out.